Efecto del Supermagroy Fosfoactiven el cultivo de Trigo en el semiárido Bonaerense - Mediavilla Hernandez, María Clara; Tranier Perez, Elián Alberto; Flores, Carlos; Poo, Juan Ignacio; Lauro, M.; Escorriza, M. (Universidad Nacional de Jujuy, 2025)
Poster y ponencia